Barriers and facilitators to participation in physical activity for students with disabilities in an integrated school setting: a meta-synthesis of qualitative research evidence - Liu, Xinyi; Han, Haijun; Li, Zhendong; Huang, Shouzhen; Zhao, Yijia; Xiao, Qian; Sun, Jingquan (Frontiers in Public Health, 2025)
PurposeThis review investigates the factors influencing the participation of students with disabilities (SWD) in physical activities (PA) within integrated school settings.Materials and methodsA keyword search of articles published up to May 2024 identified 22 studies meeting the inclusion criteria. Thematic synthesis was used to analyze the data, resulting in a dynamic theoretical model.ResultsThe model encompasses 19 themes, including an individual-level “Special factor” and three phases: perspectives from school administrators (First phase), a two-way dialogue between school management and staff (Second phase), and interactions among staff, SWD, and peers (Third phase). The final phase, based on basic psychological needs theory, identifies autonomy, competence, and relatedness needs.ConclusionThe dynamic model highlights that no single factor fully explains SWD participation in PA within inclusive environments. Educators must consider physiological, behavioral, and cognitive aspects, as well as mediating factors and processes (three phases), to design tailored strategies that address SWD needs and foster a supportive environment.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024577620.